PERAN GENERASI MUDA DALAM MENGELOLA MEDIA SOSIAL SECARA PRODUKTIF DI SMA PGRI 2 DEPOK - Alhayu Rifhatul Fikriyah; Indah Nurfebriani; Rheva Deo Pratama (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
The development of information and communication technology in the digital era has brought about significant changes in people's lives, particularly in communication patterns, information dissemination, and social interaction. The presence of social media makes it easy for people to obtain information, build communication, expand social networks, and develop creativity without being limited by space and time. However, uncontrolled use of social media can lead to various negative impacts such as digital addiction, the spread of fake news (hoaxes), cyberbullying, and decreased productivity. This Community Service (PKM) activity was conducted by students of the Faculty of Economics and Business, Pamulang University, at SMA PGRI 2 Depok on May 21, 2026, with the theme "The Role of the Younger Generation in Managing Social Media Productively." This activity aimed to educate students about the positive, creative, productive, and responsible use of social media. The activity was implemented through material delivery, interactive discussions, digital literacy education, and a question-and-answer session regarding the use of social media in the digital age. The results of the activity demonstrated high student enthusiasm for the material presented. Participants gained an understanding of the importance of using social media as a learning tool, developing creativity, personal branding, and even digital business opportunities. Furthermore, students learned about social media ethics, personal data security, and the importance of filtering information before sharing it with others. Through this activity, it is hoped that the younger generation will be able to use social media more wisely, creatively, and productively, thus providing positive benefits for personal development and the surrounding environment.